A taxonomic revision of Phytophthora Clade 5 including two new species, Phytophthora agathidicida and P. cocois - Weir, Bevan Simon; Paderes, Elsa P.; Anand, Nitish; Uchida, Janice Y.; Pennycook, Shaun R.; Bellgard, Stanley E.; Beever, Ross E. (Phytotaxa, 2015)
Phytophthora Clade 5 is a very poorly studied group of species of oomycete chromists, consisting of only two known species P. castaneae (≡ P. katsurae, nom. illegit.) and P. heveae with most isolates from East Asia and the Pacific Islands. However, isolates of two important disease-causing chromists in Clade 5, one of kauri (Agathis australis) in New Zealand, the other of coconut (Cocos nucifera) in Hawaii, poorly match the current species descriptions. To verify whether these isolates belong to separate species a detailed morphological study and phylogenetic analysis consisting of eight genetic loci was conducted. On the basis of genetic and morphological differences and host speciﬁcity, we present the formal description of two new species in Clade 5, Phytophthora agathidicida sp. nov. and Phytophthora cocois sp. nov. To clarify the typification of the other Clade 5 species, an authentic ex-holotype culture of Phytophthora castaneae is designated and P. heveae is lectotypified and epitypified.